2018
DOI: 10.21003/ea.v168-13
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of public financial control in the context of ensuring financial security of the state

Abstract: Abstract. Increasing threats to financial security are one of the major economic problems in Ukraine in terms of accelerated globalisation of the world economy against the background of overcoming the global financial crisis. It is required to improve public financial control (PFC) to provide an effective response to real threats in the financial sector. The article summarises the shortcomings inherent in the public financial control at the current stage of its development. The authors of the article have dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…To salvage this, studies have suggested adoptions of better internal systems for controlling the operations of the NGOs and ensuring prevention of fraudulent activities (Omwaka & Wanyoike, 2016;Kituku, 2014;Rotich, 2014). Empirical studies suggest that effectiveness of internal financial controls should be considered critical because its purpose is ostensibly to detect and prevent fraud and errors which can adversely affect organizations financial performance (Meiss, Naumik-Gladka, Krivtsova, & Liadova, 2017;Dikan, Deineko, & Kalinkin, 2017;Isroilov, Abduganiyev, & Ibragimov, 2020). According to Kembauw, Munawar, Purwanto, Budiasih, and Utami (2020), an effective financial control is critical in ensuring that organizational resources are allocated and utilized in an open, responsible and accountable manner, so as to ensure the operational and financial goals of the organization are met.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…To salvage this, studies have suggested adoptions of better internal systems for controlling the operations of the NGOs and ensuring prevention of fraudulent activities (Omwaka & Wanyoike, 2016;Kituku, 2014;Rotich, 2014). Empirical studies suggest that effectiveness of internal financial controls should be considered critical because its purpose is ostensibly to detect and prevent fraud and errors which can adversely affect organizations financial performance (Meiss, Naumik-Gladka, Krivtsova, & Liadova, 2017;Dikan, Deineko, & Kalinkin, 2017;Isroilov, Abduganiyev, & Ibragimov, 2020). According to Kembauw, Munawar, Purwanto, Budiasih, and Utami (2020), an effective financial control is critical in ensuring that organizational resources are allocated and utilized in an open, responsible and accountable manner, so as to ensure the operational and financial goals of the organization are met.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Impact assessment involves assessing the consequences if the risk is realized. So impact assessment does not take into account the likelihood, it merely answers the question of what will happen if a particular event comes to fruition (Meiss. et.…”
Section: Coso Risk Assessment Guidelinesmentioning
confidence: 99%
“…Theoretical, methodological and praxeological principles of state's economic security development are a subject of scientific researches of numerous domestic and foreign authors. Meiss et al (2017) focus their attention on state's financial security as a component of economic security. According to mentioned scientists, state financial control has the biggest influence on state's financial security.…”
Section: Literature Reviewmentioning
confidence: 99%